Gasto sanitario público y mortalidad por COVID-19 en España y en Europa - Elola-Somoza, F.J. (Rev Clin Esp, 2021)
OBJECTIVE: To analyze the association between public health expenditure per capita and the mortality rate due to COVID-19 in Europe and Spain. MATERIAL AND METHODS: Pearson's correlation coefficient was used to compare and contrast the mortality rate due to COVID-19 between countries and autonomous communities with higher and lower public health expenditure per capita than the mean. RESULTS: No correlation between the public health expenditure per capita and the mortality rate due to COVID-19 (r: 0.3; p = 0.14) was found among European countries or Spain's Autonomous Communities (r: 0.03; p = 0.91). No significant differences were found when comparing the mortality rate due to COVID-19 among the public health expenditure per capita groups. CONCLUSIONS: The available evidence does not support association between «low» public healthcare expenditure and the poor outcomes observed in Spain during the COVID-19 pandemic. Increased funding for the Spanish National Health System should be earmarked for structural reforms to increase its social efficiency.